2008
DOI: 10.1161/circresaha.107.162230
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Nitric Oxide Causes Age-Associated Impairment of Circadian Rhythmicity

Abstract: Abstract-Impairment of circadian rhythmicity in the elderly has been suggested to cause age-associated diseases such as atherosclerosis and hypertension. Endothelium-derived nitric oxide (NO) is a critical regulator of cardiovascular homeostasis, but its production declines with aging, thereby inducing vascular dysfunction. We show here that impaired circadian rhythmicity is related to a decrease of NO production with aging. Treatment with an NO donor significantly upregulated the promoter activity of the cloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 45 publications
2
77
0
1
Order By: Relevance
“…This suggests that NO causes diurnal fluctuations in medullary oxygenation. NO is involved in the regulation of circadian rhythmicity in blood pressure 28, 29, 30. A shift in peak blood pressure of 4 hours was found in the current study.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This suggests that NO causes diurnal fluctuations in medullary oxygenation. NO is involved in the regulation of circadian rhythmicity in blood pressure 28, 29, 30. A shift in peak blood pressure of 4 hours was found in the current study.…”
Section: Discussionsupporting
confidence: 70%
“…Healthy renal pO 2 in cortex and medulla shows circadian rhythmicity 27. NO depletion is known to affect the diurnal rhythm of blood pressure in rodents,28, 29, 30 but effects on renal oxygenation circadian rhythm are as yet unknown.…”
Section: Introductionmentioning
confidence: 99%
“…We (36) have previously demonstrated that Per1 KO mice have significantly reduced BP compared with WT control mice. It is likely that multiple other factors contribute to the BP phenotype of these circadian mutant mice, including sympathetic activity (33,37), the heart (13), nitric oxide (19), and the vasculature (4). Interestingly, a recent report (24) using gene expression profiling in normotensive and hypertensive humans of white European ancestry discovered that Per1 was overexpressed in the renal medulla of hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another study has shown similar effects in Per2 KO mice in that aortic rings from Per2 KO mice exhibited impaired endothelium-dependent relaxation from acetylcholine (150). An interesting study demonstrated that nitric oxide can activate Per1 gene expression through a cAMP response element binding protein (cREB) and CLOCK/BMAL1-dependent mechanism (66). In the same study it was also demonstrated that age-dependent decreases in nitric oxide were related to impaired circadian rhythmicity.…”
Section: Cardiovascular System and The Kidneymentioning
confidence: 77%
“…Supine positioning at night does not appear to be required for rhythmic blood pressure in normotensive males and females (123). It is likely that a combination of factors including sympathetic activity (85,138), hormone signaling (37), nitric oxide (66), and sodium reabsorption all contribute in some way to circadian blood pressure control. Much work is needed to determine which factors or mechanisms are involved in the circadian control of blood pressure.…”
Section: Cardiovascular System and The Kidneymentioning
confidence: 99%